An Alternative to the Continued Accumulation of Separated Plutonium in Japan: Dry Cask Storage of Spent Fuel. Issue 2 (3rd July 2018) - Takubo, Masafumi; Von Hippel, Frank N.
ABSTRACT: As of the end of 2017, Japan had a stockpile of 48 tons of separated plutonium. It will take more than a decade for Japan to convert most of that plutonium into "mixed-oxide" (MOX) fuel and load it into power reactors licensed to use such fuel. This is a very costly program. Including the cost of reprocessing, MOX fuel costs about ten times more than the low-enriched-uranium fuel that otherwise would be used by these reactors. Yet Japan has a policy to start separating more plutonium from spent reactor fuel as soon as the Rokkasho Reprocessing Plant can be put into operation – currently projected for 2021 after 24 years of delay due to a variety of technical problems and upgrades in safety requirements. Japan's government remains committed to this costly and troubled program primarily because, pending the availability of additional spent-fuel storage space on or off site, reprocessing is seen as the only way to get spent fuel out of reactor pools that are getting full. Because of concerns about the safety of dense-packed spent-fuel pools, however, the prefectures and towns hosting Japan's power reactors are beginning to accept on-site storage of spent fuel in dry casks. This is the option the United States and many other countries chose after they cancelled their reprocessing programs and their powerplant pools filled up. Its increasing availability in Japan, if backed by a determined policy to accelerate its introduction, should make it possible to cancel reprocessing in Japan as well.